A lithium manganese iron phosphate composite material and its preparation method and application

By introducing phosphate-modified graphene oxide and polyvinyl alcohol into the lithium manganese iron phosphate positive electrode material, combined with manganese, lithium and iron sources, three-dimensional structural composite materials were prepared by hydrothermal method and chemical oxidation polymerization, the problem of poor conductivity of lithium manganese iron phosphate was solved and its electrochemical performance and stability were significantly improved.

CN119330327BActive Publication Date: 2025-03-07HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411871584.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-07
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing lithium manganese iron phosphate positive electrode materials have poor electrical conductivity, which affects its discharge specific capacity and rate performance.

Method used

By conducting a phosphate esterification reaction on graphene oxide and polyvinyl alcohol, combining manganese, lithium and iron sources, a mixed solution is prepared by hydrothermal method, and a three-dimensional structure of manganese iron phosphate composite material is obtained by calcining and chemical oxidation polymerization.

Benefits of technology

It significantly improves the conductivity of lithium manganese iron phosphate, improves its specific capacity, circulation performance and rate performance, and enhances the stability of the material and the charging and discharging performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330327B_ABST
    Figure CN119330327B_ABST
Patent Text Reader

Abstract

The invention discloses a lithium iron manganese phosphate composite material and a preparation method and application thereof, belonging to the technical field of lithium batteries. The composite material comprises the following raw materials: a lithium source, a manganese source, an iron source, phytic acid, graphene oxide, polyvinyl alcohol, pyrrole and a dopant. The invention adopts a hydrothermal method to make hydroxyl groups on the surface of graphene oxide react with phytic acid to obtain a mixed solution a, and similarly obtains a mixed solution b containing polyvinyl alcohol phytate, combines a manganese source, a lithium source and an iron source, prepares a semi-finished product by roasting, and then coats a doped polypyrrole layer on the surface of the semi-finished product to finally obtain a lithium iron manganese phosphate composite material with a three-dimensional structure. The three-dimensional structure is a composite structure of a rod-like structure and a sheet structure. Compared with the lithium iron manganese phosphate material with a single morphology in the prior art, the specific surface area is significantly improved, the stability is stronger, the contact area with the electrolyte is larger, and the diffusion efficiency of lithium ions and the charge and discharge performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a lithium manganese iron phosphate composite material and a preparation method and application thereof. Background Art

[0002] Compared with lithium iron phosphate, lithium manganese iron phosphate has a high voltage platform, and its energy density is about 3 times that of lead-acid batteries and 2.5 times that of nickel-chromium batteries. At room temperature 0.33C charging and discharging, the capacity of lithium manganese iron phosphate battery cells is still greater than 80% after 2000 cycles, while the cycle life of lead-acid batteries is about 300 times. The service life of lead-acid batteries generally does not exceed 5 years, while the service life of lithium manganese iron phosphate batteries can be as high as 8-10 years.

[0003] However, in terms of electron transport capacity, the conductivity of lithium manganese iron phosphate is lower than that of lithium iron phosphate with semiconductor properties. The conductivity of lithium iron phosphate is 10 -9 S / cm, lithium manganese iron phosphate is only 10 -13 S / cm. This low conductivity leads to low transmission efficiency of electrons and ions in lithium manganese iron phosphate during charging and discharging, thus affecting its discharge specific capacity and rate performance.

[0004] Therefore, providing a highly conductive lithium manganese iron phosphate composite material is a technical problem that needs to be solved at present. Summary of the invention

[0005] The purpose of the present invention is to provide a lithium iron manganese phosphate composite material and a preparation method and application thereof, aiming to solve the problem of poor conductivity of existing lithium iron manganese phosphate positive electrode materials.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A method for preparing a lithium manganese iron phosphate composite material comprises the following steps:

[0008] S1. Add graphene oxide to deionized water, add phytic acid after ultrasonic dispersion for 3-4 hours, continue ultrasonic dispersion for 30 minutes, stir and react at 100°C for 12 hours to obtain a mixed solution a; add polyvinyl alcohol and urea to deionized water, stir at 100°C for 20 minutes, then add phytic acid, stir and react at 100-110°C for 2 hours to obtain a mixed solution b;

[0009] S2, mixing the mixed solution b and the mixed solution a to obtain a mixed solution c, adding a manganese source and an iron source into deionized water, stirring to obtain a metal mixed solution, adding the metal mixed solution into the mixed solution c, heating at 50-80°C for 12 hours at a rotation speed of 400-600 rpm, then cooling to room temperature, filtering, washing and drying the filter cake to obtain a first precursor; mixing the first precursor, a lithium source and deionized water, stirring at 400-500 rpm for 6 hours, and then drying in an oven at 80°C to constant weight to obtain a second precursor;

[0010] S3, placing the second precursor in a tube furnace, calcining at 500-800°C for 6-10h under nitrogen protection, naturally cooling to room temperature, and crushing to obtain a semi-finished product with a particle size D50 of 0.5-2.5μm;

[0011] S4. Add the semi-finished product, pyrrole and dopant into deionized water, stir evenly, then add ferric chloride solution, stir at 20-30°C for 7h, then filter, wash and dry the filter cake to obtain a lithium iron manganese phosphate composite material. The semi-finished product is used as a substrate, pyrrole is used as a monomer, and ferric chloride is used as an oxidant to obtain a lithium iron manganese phosphate composite material containing doped polypyrrole through chemical oxidation polymerization.

[0012] Furthermore, the lithium source is at least one of lithium carbonate, lithium oxalate, lithium acetate and lithium nitrate.

[0013] Furthermore, the manganese source is at least one of manganese sulfate, manganese nitrate and manganese chloride.

[0014] Furthermore, the iron source is at least one of ferrous sulfate, ferrous nitrate and ferrous chloride.

[0015] Furthermore, the number of graphene oxide layers is 1-5.

[0016] Furthermore, the average molecular weight of the polyvinyl alcohol is 16,000-20,000.

[0017] Furthermore, the dopant is dodecylbenzenesulfonic acid and / or potassium perfluorooctanesulfonate.

[0018] Furthermore, the molar ratio of manganese element, iron element, lithium element and phosphorus element in the manganese source, iron source, lithium source and phytic acid is (0.4-0.6):(0.4-0.6):(1.02-1.05):1.

[0019] Furthermore, the mass ratio of the amount of phytic acid added in the mixed solution a to the amount of phytic acid added in the mixed solution b is 2.1-3.5:12-13.

[0020] Furthermore, the usage ratio of graphene oxide, deionized water and phytic acid in the mixed solution a is 0.15 g: 100-200 mL: 2.1-3.5 g.

[0021] Furthermore, the dosage ratio of polyvinyl alcohol, urea, deionized water and phytic acid in the mixed solution b is 0.8 g:4 g:100 mL:12-13 g.

[0022] Furthermore, the amount of deionized water in the metal mixed solution is 8-10 times the total mass of the manganese source and the iron source.

[0023] Furthermore, the amount of deionized water used in the preparation process of the second precursor is 10 times the mass of the lithium source.

[0024] Furthermore, the heating rate of the tubular furnace is 5-10°C / min.

[0025] Furthermore, in step S4, the dosage ratio of the semi-finished product, pyrrole, dopant, deionized water and ferric chloride solution is 3g: 0.25-0.5g: 0.01-0.06g: 100mL: 10mL, and the mass fraction of ferric chloride in the ferric chloride solution is 3-4%.

[0026] A lithium manganese iron phosphate composite material is prepared by the above preparation method.

[0027] The invention discloses an application of lithium iron manganese phosphate composite material in lithium ion batteries.

[0028] Beneficial effects of the present invention:

[0029] 1. The present invention uses phytic acid as a phosphorus source, and adopts a hydrothermal method to make the hydroxyl groups on the surface of graphene oxide react with phytic acid to undergo a phosphate esterification reaction, so as to obtain a mixed solution a containing phytic acid-modified graphene oxide. Similarly, the hydroxyl groups of polyvinyl alcohol react with phytic acid to undergo a phosphate esterification reaction, so as to obtain a mixed solution b containing polyvinyl alcohol phytate. Based on this, in combination with a manganese source, a lithium source, and an iron source, lithium iron manganese phosphate particles are grown along the lamellar graphene and the linear polyvinyl alcohol molecular chain, and a semi-finished product is prepared by calcination. Then, doped polypyrrole is carried on the surface of the semi-finished product, and finally a lithium iron manganese phosphate composite material with a three-dimensional structure is obtained. The three-dimensional structure is a composite structure of a rod-like structure and a lamellar structure. Compared with the lithium iron manganese phosphate material with a single morphology in the prior art, the specific surface area is significantly improved, the stability is stronger, and there is a larger contact area with the electrolyte, thereby improving the diffusion efficiency of lithium ions and the charge and discharge performance of the battery.

[0030] 2. The lithium manganese iron phosphate composite material of the present invention contains doped polypyrrole on the outside and a graphene carbon network on the inside. Based on the good electrical conductivity of the doped polypyrrole and the graphene carbon network, the electrical conductivity of the lithium manganese iron phosphate is significantly improved, so that the obtained lithium manganese iron phosphate composite material has a high specific capacity, good cycle performance, and excellent rate performance.

[0031] 3. The introduction of doped polypyrrole in the present invention, on the one hand, strengthens the conductivity of the lithium iron manganese phosphate composite material, and on the other hand, utilizes the good stability of polypyrrole under acidic conditions to reduce manganese dissolution, and weakens the problems of low discharge specific capacity and poor cycle performance introduced in the lithium iron manganese phosphate composite material due to manganese dissolution. In addition, the mass ratio between pyrrole and the semi-finished product should be reasonably controlled. If the amount of pyrrole is too low, the doped polypyrrole on the surface of the semi-finished product is too little, and the conductivity is small, which leads to a low discharge specific capacity of the material. If the amount of pyrrole is too high, the doped polypyrrole on the surface of the semi-finished product will be too much, which will increase the lithium ion migration distance during the charging process, reduce the lithium ion diffusion coefficient of the material, and the discharge specific capacity will also be reduced.

[0032] 4. The introduction of dopants in the doped polypyrrole of the present invention can optimize the conductive properties of the lithium iron manganese phosphate composite material on the one hand, and on the other hand, combined with the low surface energy characteristics of the dopant itself, it can improve the hydrophobic properties of the lithium iron manganese phosphate composite material, reduce the water absorption rate, and reduce the enrichment of water on its surface during the preparation of the lithium iron manganese phosphate composite material, thereby improving the stability of the surface structure of the positive electrode material and optimizing the cycle stability of the battery. However, if too much dopant is introduced, the degree of separation of the polypyrrole molecular chain will increase, carrier jumping will be blocked, and the dopant itself has no conductivity, which will reduce the conductive properties of the lithium iron manganese phosphate composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The present invention will be further described below in conjunction with the accompanying drawings.

[0034] Figure 1 This is a SEM image of the lithium manganese iron phosphate composite material of Example 1 of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] A method for preparing a lithium manganese iron phosphate composite material comprises the following steps:

[0038] S1. Add 1.17 g of graphene oxide (1-5 layers) to 780 mL of deionized water, add 16.4 g of phytic acid after ultrasonic dispersion for 3 h, continue ultrasonication for 30 min, stir and react at 100 ° C for 12 h to obtain a mixed solution a; add 6.24 g of polyvinyl alcohol (average molecular weight of 16000) and 31.2 g of urea to 780 mL of deionized water, stir at 100 ° C for 20 min, then add 93.6 g of phytic acid, stir and react at 100 ° C for 2 h to obtain a mixed solution b;

[0039] S2, adding mixed solution b to mixed solution a, stirring evenly to obtain mixed solution c, adding 0.6 mol manganese sulfate and 0.4 mol ferrous sulfate to 1.21 L deionized water, stirring evenly to obtain a metal mixed solution, adding the metal mixed solution to mixed solution c, heating at 50°C for 12 h at a speed of 400 rpm, then cooling to room temperature, filtering, washing the filter cake with deionized water and drying it in an oven at 60°C for 24 h to obtain a first precursor; mixing the first precursor, 1.02 mol lithium acetate and 1.04 L deionized water, stirring at 400 rpm for 6 h, and then drying in an oven at 80°C to constant weight to obtain a second precursor;

[0040] S3, placing the second precursor in a tube furnace, heating the temperature to 500°C at a heating rate of 5°C / min under nitrogen protection, calcining for 10 hours, naturally cooling to room temperature, and crushing to obtain a semi-finished product with a particle size D50 of 0.5-2.5 μm;

[0041] S4. Add 30 g of the semi-finished product, 2.5 g of pyrrole and 0.6 g of dodecylbenzenesulfonic acid to 1 L of deionized water, stir evenly, then add 100 mL of ferric chloride solution, stir at 20 ° C for 7 hours, then filter, wash the filter cake with deionized water and place it in an oven at 60 ° C for 24 hours to obtain a manganese iron phosphate lithium composite material, the mass fraction of ferric chloride in the ferric chloride solution is 3%.

[0042] The lithium manganese iron phosphate composite material prepared in Example 1 was observed microscopically using an electron microscope. Figure 1 As shown by Figure 1 It can be seen that the lithium manganese iron phosphate composite material has a composite structure of a rod-like structure and a lamellar structure.

[0043] Example 2

[0044] A method for preparing a lithium manganese iron phosphate composite material comprises the following steps:

[0045] S1. Add 1.07 g of graphene oxide (1-5 layers) to 710 mL of deionized water, add 21.3 g of phytic acid after ultrasonic dispersion for 3.5 h, continue ultrasonication for 30 min, stir and react at 100 ° C for 12 h to obtain a mixed solution a; add 5.68 g of polyvinyl alcohol (average molecular weight of 20,000) and 28.38 g of urea to 709.6 mL of deionized water, stir at 100 ° C for 20 min, then add 88.7 g of phytic acid, stir and react at 105 ° C for 2 h to obtain a mixed solution b;

[0046] S2, adding mixed solution b to mixed solution a, stirring evenly to obtain mixed solution c, adding 0.5 mol manganese nitrate and 0.5 mol ferrous nitrate to 1.79 L deionized water, stirring evenly to obtain a metal mixed solution, adding the metal mixed solution to mixed solution c, heating at 60°C for 12 h at a speed of 500 rpm, then cooling to room temperature, filtering, washing the filter cake with deionized water and drying it in an oven at 60°C for 24 h to obtain a first precursor; mixing the first precursor, 1.03 mol lithium nitrate and 710.2 mL deionized water, stirring at 450 rpm for 6 h, and then drying in an oven at 80°C to constant weight to obtain a second precursor;

[0047] S3, placing the second precursor in a tube furnace, heating the temperature to 650°C at a heating rate of 8°C / min under nitrogen protection, calcining for 9 hours, naturally cooling to room temperature, and crushing to obtain a semi-finished product with a particle size D50 of 0.5-2.5 μm;

[0048] S4. Add 30g of the semi-finished product, 3.5g of pyrrole and 0.3g of potassium perfluorooctane sulfonate to 1L of deionized water, stir evenly, then add 100mL of ferric chloride solution, stir at 25°C for 7h, then filter, wash the filter cake with deionized water and place it in an oven at 60°C for drying for 24h to obtain a manganese iron phosphate lithium composite material, and the mass fraction of ferric chloride in the ferric chloride solution is 3.5%.

[0049] Example 3

[0050] A method for preparing a lithium manganese iron phosphate composite material comprises the following steps:

[0051] S1. Add 1.0 g of graphene oxide (1-5 layers) to 665.7 mL of deionized water, add 23.3 g of phytic acid after ultrasonic dispersion for 4 h, continue ultrasonication for 30 min, stir and react at 100 ° C for 12 h to obtain a mixed solution a; add 5.34 g of polyvinyl alcohol (average molecular weight of 20,000) and 26.68 g of urea to 666.9 mL of deionized water, stir at 100 ° C for 20 min, then add 86.7 g of phytic acid, stir and react at 110 ° C for 2 h to obtain a mixed solution b;

[0052] S2, adding mixed solution b to mixed solution a, stirring evenly to obtain mixed solution c, adding 0.6 mol manganese chloride and 0.4 mol ferrous chloride to 1.26 L deionized water, stirring evenly to obtain a metal mixed solution, adding the metal mixed solution to mixed solution c, heating at 80°C for 12 h at a speed of 600 rpm, then cooling to room temperature, filtering, washing the filter cake with deionized water and drying it in an oven at 60°C for 24 h to obtain a first precursor; mixing the first precursor, 1.05 mol lithium nitrate and 723.98 mL deionized water, stirring at 500 rpm for 6 h, and then drying in an oven at 80°C to constant weight to obtain a second precursor;

[0053] S3, placing the second precursor in a tube furnace, heating the temperature to 800°C at a heating rate of 10°C / min under nitrogen protection, calcining for 10 hours, naturally cooling to room temperature, and crushing to obtain a semi-finished product with a particle size D50 of 0.5-2.5 μm;

[0054] S4. Add 30g of the semi-finished product, 5g of pyrrole and 0.1g of potassium perfluorooctane sulfonate to 1L of deionized water, stir evenly, then add 100mL of ferric chloride solution, stir at 30°C for 7h, then filter, wash the filter cake with deionized water and dry it in an oven at 60°C for 24h to obtain a manganese iron phosphate lithium composite material, and the mass fraction of ferric chloride in the ferric chloride solution is 4%.

[0055] Comparative Example 1

[0056] A method for preparing a lithium manganese iron phosphate composite material is different from Example 1 only in that the mixed solution a is different. The comparative mixed solution a is obtained by ultrasonically mixing 780 mL of deionized water and 16.4 g of phytic acid for 30 minutes.

[0057] Comparative Example 2

[0058] A method for preparing a lithium manganese iron phosphate composite material is different from Example 1 only in that the mixed solution b is different. The comparative mixed solution b is obtained by stirring and mixing 780 mL of deionized water and 93.6 g of phytic acid for 2 hours.

[0059] Comparative Example 3

[0060] A method for preparing a lithium manganese iron phosphate composite material, which is different from Example 1 only in that mixed solution a and mixed solution b are different. Mixed solution a is obtained by ultrasonically mixing 1.17g of graphene oxide (the number of layers is 1-5), 780mL of deionized water and 16.4g of phytic acid for 30 minutes, and mixed solution b is obtained by stirring and mixing 6.24g of polyvinyl alcohol (average molecular weight is 16000), 780mL of deionized water and 93.6g of phytic acid for 2h.

[0061] Comparative Example 4

[0062] A method for preparing a lithium manganese iron phosphate composite material, which is different from Example 1 only in that mixed solution a and mixed solution b are different, mixed solution a is obtained by ultrasonically mixing 780 mL of deionized water and 16.4 g of phytic acid for 30 minutes, and mixed solution b is obtained by stirring and mixing 780 mL of deionized water and 93.6 g of phytic acid for 2 hours.

[0063] Comparative Example 5

[0064] A method for preparing a lithium manganese iron phosphate composite material is different from Example 1 only in that the amount of pyrrole in Example 1 is adjusted from 2.5 g to 2.0 g.

[0065] Comparative Example 6

[0066] A method for preparing a lithium manganese iron phosphate composite material is different from Example 3 only in that the amount of pyrrole in Example 3 is adjusted from 5.0 g to 5.5 g.

[0067] Comparative Example 7

[0068] A method for preparing a lithium manganese iron phosphate composite material, which is different from Example 3 only in that potassium perfluorooctane sulfonate is not added.

[0069] Comparative Example 8

[0070] A method for preparing a lithium manganese iron phosphate composite material is different from Example 1 only in that the amount of dodecylbenzenesulfonic acid in Example 1 is adjusted from 0.6 g to 0.7 g.

[0071] The lithium manganese iron phosphate composite materials obtained from Examples 1 to 3 and Comparative Examples 1 to 8 were tested:

[0072] Specific surface area: The test was conducted using the Jin'ep V-Sorb2800 equipment. The lithium manganese iron phosphate composite material sample was pre-treated and dried at 150°C for 2 hours using the static method.

[0073] Powder resistivity: using the four-probe method, the test pressure is 10MPa;

[0074] Manganese dissolution: 10 g of lithium manganese iron phosphate composite material was added to 90 g of 0.1 mol / L hydrochloric acid solution, stirred and mixed at 25°C for 30 min, and then filtered. The manganese element in the obtained filtrate was measured by ICP to obtain manganese dissolution data;

[0075] Water absorption: The initial water content MO of each group of lithium manganese iron phosphate composite materials was tested, and then placed in the air. The water absorption M1 was tested again after 7 days. The water absorption = M1-MO;

[0076] The test results are shown in Table 1:

[0077]

[0078] It can be seen from the data recorded in Table 1 that the specific surface area of ​​the lithium manganese iron phosphate composite material obtained in Examples 1-3 is 15.1-16.2 m 2 / g, powder resistivity is 96.8-99.0Ω·cm, manganese dissolution is 8.4-10.3ppm, water absorption is 20-28ppm, and comprehensive performance is good; specifically, it can be seen from the test results of Example 1 and Comparative Example 1 that the absence of graphene oxide will lead to a significant decrease in the conductivity and specific surface area of ​​the lithium iron manganese phosphate composite material; it can be seen from the test results of Example 1 and Comparative Example 2 that the absence of polyvinyl alcohol will also lead to a significant decrease in the conductivity and specific surface area of ​​the lithium iron manganese phosphate composite material; it can be seen from the test results of Example 1 and Comparative Example 3 that the step of "stirring the reaction at 100°C for 12h" is omitted in the preparation process of the mixed solution a and the mixed solution b, which will also lead to a significant decrease in the conductivity and specific surface area of ​​the lithium iron manganese phosphate composite material; it can be seen from the test results of Example 1 and Comparative Example 4 , the common absence of graphene oxide and polyvinyl alcohol will lead to different degrees of decrease in the specific surface area, conductivity, manganese dissolution and water absorption performance of the lithium iron manganese phosphate composite material; compared with Example 1 and Comparative Example 5, the amount of pyrrole is lower, and compared with Example 3 and Comparative Example 6, the amount of pyrrole is higher, which exceeds the mass ratio range between pyrrole and the semi-finished product of the present invention. It can be seen from the test results in Example 1, Comparative Example 5 and Example 3 and Comparative Example 6 that too high and too low an amount of pyrrole will have a significant adverse effect on the conductivity and manganese dissolution performance of the lithium iron manganese phosphate composite material; similarly, it can be seen from the test results in Example 1, Comparative Example 8 and Example 3 and Comparative Example 7 that the absence and excessive use of dopants will have a significant adverse effect on the conductivity, manganese dissolution and water absorption of the lithium iron manganese phosphate composite material.

[0079] The electrochemical performance test of the lithium iron manganese phosphate composite material prepared in Examples 1-3 and Comparative Examples 1-8 was conducted using a button cell, and the positive electrode active material was the lithium iron manganese phosphate composite material prepared in Examples 1-3 and Comparative Examples 1-8, respectively, wherein the conductive agent was Super P, the binder was polyvinylidene fluoride, the solvent was a dimethyl carbonate (DMC) and ethylene carbonate (EC) solution with a volume ratio of 1:1, the mass ratio of the positive electrode active material, the conductive agent and the binder was 8:1:1, the negative electrode was a lithium sheet, the diaphragm was a Celgard 2500 composite membrane, and the electrolyte was 1 mol / L lithium hexafluorophosphate; the button cell was assembled in an argon protective atmosphere glove box. The electrochemical performance test of the button cell was conducted using a blue electric test cabinet, the test temperature was 25°C, the test voltage range was set to 2V-4.5V, and the test results are shown in Table 2:

[0080]

[0081] It can be seen from the data recorded in Table 2 that, compared with Comparative Examples 1-8, the lithium manganese iron phosphate composite material obtained in Examples 1-3 has better electrochemical performance, high specific capacity, good cycle performance, and excellent rate performance.

[0082] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a lithium manganese iron phosphate composite material, characterized in that: The following steps are involved: S1. Add graphene oxide to deionized water, add phytic acid after ultrasonic dispersion for 3-4 hours, continue ultrasonic dispersion for 30 minutes, stir and react at 100°C for 12 hours to obtain a mixed solution a; add polyvinyl alcohol and urea to deionized water, stir at 100°C for 20 minutes, then add phytic acid, stir and react at 100-110°C for 2 hours to obtain a mixed solution b; S2, mixing the mixed solution b and the mixed solution a to obtain a mixed solution c, adding a manganese source and an iron source into deionized water, stirring to obtain a metal mixed solution, adding the metal mixed solution into the mixed solution c, heating at 50-80°C for 12 hours, cooling to room temperature, filtering, washing and drying the filter cake to obtain a first precursor; mixing the first precursor, a lithium source and deionized water, stirring for 6 hours, and drying to obtain a second precursor; S3, calcining the second precursor at 500-800°C for 6-10h under nitrogen protection, naturally cooling to room temperature, and crushing to obtain a semi-finished product; S4, adding the semi-finished product, pyrrole and dopant into deionized water, stirring evenly, adding ferric chloride solution, stirring at 20-30° C. for 7 h, filtering with suction, washing and drying the filter cake, and obtaining a manganese iron phosphate lithium composite material; The doping agent is dodecylbenzenesulfonic acid and / or potassium perfluorooctanesulfonate; In step S4, the dosage ratio of the semi-finished product, pyrrole, dopant, deionized water and ferric chloride solution is 3g: 0.25-0.5g: 0.01-0.06g: 100mL: 10mL, and the mass fraction of ferric chloride in the ferric chloride solution is 3-4%.

2. The method for preparing a lithium iron manganese phosphate composite material according to claim 1, characterized in that: The number of graphene oxide layers is 1-5.

3. The method for preparing a lithium iron manganese phosphate composite material according to claim 1, characterized in that: The average molecular weight of polyvinyl alcohol is 16000-20000.

4. The method for preparing a lithium iron manganese phosphate composite material according to claim 1, characterized in that: The molar ratio of manganese, iron, lithium and phosphorus in the manganese source, iron source, lithium source and phytic acid is (0.4-0.6): (0.4-0.6): (1.02-1.05):

1.

5. The method for preparing a lithium iron manganese phosphate composite material according to claim 1, characterized in that: The mass ratio of the amount of phytic acid added in the mixed solution a to the amount of phytic acid added in the mixed solution b is 2.1-3.5:12-13.

6. The method for preparing a lithium iron manganese phosphate composite material according to claim 1, characterized in that: The amount ratio of graphene oxide, deionized water and phytic acid in the mixed solution a is 0.15 g: 100-200 mL: 2.1-3.5 g, and the amount ratio of polyvinyl alcohol, urea, deionized water and phytic acid in the mixed solution b is 0.8 g: 4 g: 100 mL: 12-13 g.

7. A lithium manganese iron phosphate composite material, characterized in that: The lithium manganese iron phosphate composite material is prepared by the preparation method of any one of claims 1 to 6.

8. Use of the lithium iron manganese phosphate composite material obtained by the method for preparing the lithium iron manganese phosphate composite material according to any one of claims 1 to 6 in a lithium ion battery.

Citation Information

Patent Citations

  • Cobalt carbonate-polypyrrole composite anode material used for power lithium ion battery and preparation method thereof

    CN104157838A

  • Preparation method and application of lithium iron phosphate composite material

    CN117832427A